Komunikasi Antara Pemerintah Dan Rakyat Dalam Alquran Pada Surah Taha - Suhendri hamzah; Muhammad Ikhsan (Bashirah, 2022)
The problem studied in this study is formulated as follows: "how is the communication between the government and the people contained in the Qur'an surah Taha. This study aims to determine the form of communication between the people and the government which was exemplified by the Prophet Musa against Pharaoh in the Koran in the sura Taha, wherein this letter there is communication between a government and the people, which will make the research results This is a solution to the problem of people's communication with the government. This type of research is library research with a descriptive qualitative approach, and the primary data source is the Koran. From the results of this study, namely the communication of the people to the government, 11 important points need to be considered in communicating with the government contained in the Surah Taha.